EVALUATION OF CARDIOVASCULAR DYSREGULATION IN PATIENTS AFTER HEMORRHAGIC STROKE AS A COMPLICATION OF ESSENTIAL HYPERTENSION - Tkachyshyn, Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2021)
The aim of the study was to compare blood pressure and electrocardiogram indices, assessed by their daily monitoring, and anamnestic data on mild traumatic brain injury between a group of patients with essential hypertension ≥6 months after a hemorrhagic stroke and a group of patients with essential hypertension without complications. Materials and methods. The total number of examined patients was 198 people, who were divided into 2 groups: the main (n = 94; age – 54,4±8,8 years, M±σyears) and the control (n = 104; age – 53,7±8,9 years) one. Patients in the main group suffered a hemorrhagic stroke as a complication of essential hypertension ≥6 months ago. The control group included patients with essential hypertension, stage II. In both groups of patients, the parameters of 24-hour ambulatory blood pressure monitoring and electrocardiogram were determined. Results. The indices of 24-hour ambulatory blood pressure monitoring in the main group and the control group were the following ones, respectively:the mean daytime systolic blood pressure was 109,6±1,6 and 121,1±1,1 mm Hg, the minimal one was 74,4±2,0 mm Hg and 82,3±12,5 mm Hg, and the maximal one was 168,2±1,9 and 161,9±1,7 mm Hg, p<0,05. The daytime sigma systolic blood pressure (17,9±0,6) and its average real variability of (11,31±2,52 mm Hg) were bigger in the main group (p<0,05). The daytime index of the hyperbaric load of systolic blood pressure was bigger in the main group: it was 403,6±25,9 against 231,7±12,1 mm Hg×h in the comparison group (p<0,05). The mean, minimum and maximum heart rate at night were significantly lower in the main group (p<0,05). The QTcmin index was significantly lower in the main group in contrast to the control one – 286,28±43,34 and 336,69±22,55, and the QTvariance was greater – 232,56±44,55 –  in comparison to the control group(188,31±33,67) (p<0,05). From the anamnestic data of patients, a significantly higher prevalence of mild traumatic brain injurywas found in 37,4% (35 patients out of 94) in the main group relative to the control one – 13,5% (14 out of 104), p<0,05. Conclusions: The results of the study indicate the larger ranges of blood pressure variability in patients with essential hypertension complicated with hemorrhagic stroke, which can be caused by impaired autoregulation according to the QTc interval data. In combination with the disturbances of cerebral circulation, caused by the injury of the brain due to the hemorrhagic stroke alone or in combination with mild traumatic brain injury episode, such a situation may lead to the development of recurrent stroke.